Testosterone Functions, Uses, Deficiencies, and Substitution - Doi, Hirokazu (IntechOpen, 2023)
Testosterone regulates the physiological functions and morphology of biological organisms including humans at multiple stages of development. Understanding what is currently known about testosterone is important for specialists in many branches of science, including internal medicine, veterinary medicine, sports science, economics, cognitive neuroscience, and psychology. This book describes what is currently known about the androgenic function and its underlying mechanisms as well as reviews ethical and safety issues surrounding the clinical and practical application of achievements in testosterone research.